Cultural matching factors, child factors and fostering factors associated with successful foster placement: An explorative study into the perspectives of unaccompanied refugee children, their foster carers and guardians. (November 2020) - Rip, Jet; Zijlstra, Elianne; Post, Wendy; Kalverboer, Margrite; Knorth, Erik J.
Highlights: Quality of relationship child–carer almost one-to-one relation with placement success. Cultural similarity in foster placement; most important for child's perspective on placement success. Child, carer, guardian: different views on factors contributing to placement success. Abstract: This paper presents findings from the baseline measurement of a longitudinal Dutch study focusing on cultural matching, child and fostering factors associated with the success of foster placements of unaccompanied refugee children. We assessed the placement from the perspectives of the children, their foster carers and their guardians. The children (n = 39) and their carers (n = 37) were visited at their homes, where they completed several questionnaires (e.g. SDQ, BIC, SLE, RATS, AHIMSA and questionnaires measuring bio/demographic variables, placement success and characteristics of the placement, including cultural characteristics). The guardians (n = 37) were asked to complete a digital questionnaire. The success of the placement was analysed using logistic regression models. The quality of the relationship between child and foster carer(s) exhibited an almost one-to-one relationship with 'placement success', for both the child model and the foster carer model. This means that one could also investigate the quality of the relationship between the child and carer to determine placement success. The regression analyses showed that, for children, cultural similarity between a child and their carers was of great importance. However, for foster carers and guardians, cultural similarity was less related to placement success. In addition, a higher score on prosocial behaviour by the child (SDQ self-report) was associated with more positive outcomes regarding placement success (child model). For foster carers, children's externalizing behaviour (SDQ) was negatively correlated with the success of the placement (foster carer model). For guardians, a higher score on the quality of the caregiving environment (BIC-G) was associated with placement success (guardian model). Implications for research and practice are also discussed.